Differing risk of cancer death among patients with lymph node metastasis after radical prostatectomy and pelvic lymph node dissection: identification of risk categories according to number of positive nodes and Gleason score. (17th January 2013) - Schiavina, Riccardo; Borghesi, Marco; Brunocilla, Eugenio; Manferrari, Fabio; Fiorentino, Michelangelo; Vagnoni, Valerio; Baccos, Alessandro; Pultrone, Cristian Vincenzo; Rocca, Giovanni Christian; Rizzi, Simona; Martorana, Giuseppe
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Lymph node (LN) status is one of the most important prognostic variables in patients undergoing radical prostatectomy, but not all patients with node‐positive PCa are at the same risk of recurrence and cancer‐specific death. In this study we evaluated the role of pathological variables in stratifying the risk of cancer death in patients with prostate cancer. Patients with 1–3 positive LNs and Gleason score (GS) ≤7 experienced better CSS and OS than those with >3 metastatic LNs and/or GS >7. This evidence could allow urologists to better predict oncological outcomes of patients and select more appropriate therapeutic management. Objectives To evaluate the outcomes in patients with node‐positive prostate cancer (PCa) after radical prostatectomy (RP) and pelvic lymph node dissection (PLND) according to the number of positive lymph nodes (LNs). To identify different risk groups among patients with node‐positive PCa. Patients and Methods We evaluated 98 consecutive patients with pN1M0 PCa who underwent RP between November 1995 and May 2011. Kaplan–Meier and Cox proportional univariable and multivariable regression models were used to analyse the survival rates. Patients were divided into two groups according to number of positive LNs using the most informative positive LN theshold for predicting survival, then into three different risk groups according to number of positive LNs and pathological Gleason score (GS). Results Mean (range) follow‐up was 68.4 (10–192) months. Patients with 1–3 positive LNs (n = 75; 76.5%) had significantly better cancer‐specific survival (CSS) and overall survival (OS) compared with those with >3 positive nodes (n = 23; 23.4%; P < 0.01). Patients with 1–3 positive LNs and pathological GS ≤7 (Group 1) had significantly better CSS than those with >3 positive LNs or GS 8–10 (Group 2 [P = 0.015]). Group 2 patients, moreover, had significantly better CSS (P = 0.019) and OS (P = 0.021) than those with >3 positive LNs and GS 8–10 (Group 3). Conclusions Patients with 1–3 positive LNs have higher CSS and OS rates than those with >3 metastatic LNs. Taking into account the pathological GS, as well as the number of positive nodes, three risk group categories with considerable differences in terms of survival can be found. Patients with LN‐positive PCa should be stratified into different groups according to these two measures, to obtain a better prediction of oncological outcomes.